Some Physico-chemical Properties of Red Fruit Oil (Pandanus Conoideus Lam) from Hexane and Chloroform Fractions - Arumsari, Novita Inar; Riyanto, Sugeng; Rohman, Abdul (Journal of Food and Pharmaceutical Sciences, 2013)
As  functional  food  oil,  red  fruit  (Pandanus  conoideus  Lam)  oil  has  been  believed  by  local community  to  threat  several  degenerative  diseases  like  cancer.  Red  fruit  oil  (RFO)  has commanded high price value in Indonesian market. Therefore, the objective of the present study was to  investigate several physico-chemical properties of RFO. Some parameters of RFO  obtained  from  hexane  and  chloroform  fractions  have  been  evaluated.  Such parameters include acid value, saponification value, anisidine value, conjugated dienes and trienes as well as p-anisidine value. Besides, absorptivity coefficient, fatty acid composition, and volatile compounds were also determined. Acid value and saponification value of RFO from chloroform fraction were higher than those in RFO from hexane fraction. In addition, RFO  in hexane  fraction has  the higher  iodine and anisidine values  than  that  in chloroform fraction. Hexane  is  the  best  solvent  to  be  used  for  analysis  of  RFO,  as  indicated  by  the highest  absorptivity  coefficient  of RFO  in hexane.  The main  fatty  acid  composed  of RFO was oleic acid  followed with palmitic acid. The main volatile compound present  in RFO of hexane and chloroform fractions was 9-octadecenoic acid accounting of 41.57 % and 65.06 %, respectively.